Training plan development webinar - Steiner, T. (United World Wrestling, 2020)
Terry Steiner, USA Wrestling's Head National Coach Women`s Freestyle coach, joined Zach Errett, UWW's Education Manager, to discuss training plan development and periodization. Breakdown of the Webinar 0:01:58 - Introduction 0:06:40 - Start of his presentation 0:06:51 - Why do you need a plan? 0:08:04 - Why do we need a plan? Athlete perspective 0:10:04 - Important to have Openness and Transparency in Planning 0:10:35 - Biggest Job as National Team Coach 0:12:08 - Challenging the plan is a good thing 0:13:24 - Challenging and rewarding journey 0:14:16 - Job is helping the athletes see the value in the plan - showing the vision and including them in the process 0:14:57 - How do you start making the plan? (Things to start with) 0:16:15 - Story on Helen Maroulis 0:18:16 - How do we learn and develop the qualities? 0:20:00 - What are you going to get the most return on your investment? 0:20:53 - Basis of his 4-year plan 0:21:09 - Year 1 - Filling the Backpack 0:22:34 - Year 2 - Process Oriented 0:23:54 - Year 3 - Starting to Focus on Results 0:25:59 - Year 4 - Performing 0:27:00 - Overview of 4-year plan - Competitions and Camps 0:27:49 - Developing a Yearly Plan - Basic Process and Thoughts 0:29:52 - Science and Art in Planning 0:30:39 - Phases of the yearly plan 0:30:44 - Phase - Break time - Getting away 0:31:24 - Transition - time after the break 0:31:39 - Preparation - team focus 0:32:04 - Competition - more individual focus 0:32:34 - Peaking - rest and recovery 0:33:47 - Yearly Plan - Spreadsheet 0:36:02 - Challenge - quantifying volume and intensity 0:37:01 - Managing intensity and volume for peaking 0:38:19 - Developing a Competition Plan - last 45 days 0:38:50 - Struggle area as a young coach 0:39:21 - Story on Adeline Gray - Including in the planning process 0:41:59 - What he learned from working with Adeline Gray 0:42:49 - Managing intensity and volume during the Competition Plan 0:43:46 - Post Competition Reflection 0:44:26 - Reflection - Athlete Perspective 0:44:49 - Reflection - Coach Perspective 0:45:22 - Reflection - Data Analysis 0:46:49 - Important Data - Points by minute in a match 0:47:37 - As a coach, we need to realize it is their career 0:48:42 - Start of Q & A 0:48:52 - Can you inform the group about training load during competition phase? 0:51:22 - Is there any effects on a women`s monthly menstruation cycle? 0:53:41 - What type of information are you trying to get or asking for input when developing their training plans? 0:57:35 - How do manage to monitor athletes when they are not conducting training camps and do you perform any technical test under these conditions? 0:59:41 - What are the strategies for nutrition planning on competition days? 1:02:53 - How do you work the emotions during training and competitions? 1:06:05 - Do you arrange any fitness testing before camps and competitions? 1:07:14 - How do you measure the intensity during a macrocycle (example during pre-competition/competition phases)?